Architecture and building techniques at the Early Bronze Age site of HD-6, Rāʾs al-Ḥadd, Sultanate of Oman - Azzarà, Valentina M. (Proceedings of the Seminar for Arabian Studies, 2013)
The Hafit settlement of HD-6 at Raʾs al-Ḥadd, dated to the first half of the third millennium BC, is located in the easternmost area of the Sharqiyya region of Oman. Large-scale excavations have exposed a complex of architectural units made from mud brick and stone, built on the top of a sand dune some 200 m away from the ocean shore, and representing one of the few known habitation sites from this period. This paper will focus on building techniques and architectural patterns documented at HD-6 and propose a comparison with other Early Bronze Age sites in the Oman peninsula. Different types of mud bricks identified on site and related to successive phases of occupation, show clear differences in the composition of the paste, indicating a progression towards more elastic mud bricks and masonries more resistant to the movement of the dune below. More generally, technical characteristics of buildings hint at the progression towards structures more resistant to soil settlement. In addition, the evolution and standardization of architectural modules is perceivable in the transition from the first to the second phase of occupation. Analysis of the structures so far identified at HD-6 sheds light on the technical advancement in building methods during the first half of the third millennium BC in coastal al-Sharqiyyah.